1989
DOI: 10.1104/pp.91.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Whole Plant Senescence of Sunflower Following Seedhead Removal

Abstract: This study was undertaken to further clarify the relationship between seed development and monocarpic senescence of sunflower (Helianthus annuus L.). Field-grown plants with and without seedheads were evaluated for rate and duration of accumulation of dry weight, reduced N, and P by whole shoots, and for partitioning of these constituents within the individual plant parts.Concurrent with seedhead removal, ['5N]nitrate was applied to the plants in a selected area of the experimental plot. Whole plants (above gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Overall, it appeared that deflowering at later stage increased total dry weight in all deflowering treatments in both the years and followed increasing pattern as 35 DAS< 55 DAS< 70 DAS. Deflowered sunflower plants had a larger stem and leaf dry weight, according to previous research of Ho and Below (1989). In accordance with their findings, deflowering effect in the present study showed increased total dry weight in comparison to control (NDF) (Figure 1).…”
Section: Total Dry Mattersupporting
confidence: 92%
“…Overall, it appeared that deflowering at later stage increased total dry weight in all deflowering treatments in both the years and followed increasing pattern as 35 DAS< 55 DAS< 70 DAS. Deflowered sunflower plants had a larger stem and leaf dry weight, according to previous research of Ho and Below (1989). In accordance with their findings, deflowering effect in the present study showed increased total dry weight in comparison to control (NDF) (Figure 1).…”
Section: Total Dry Mattersupporting
confidence: 92%
“…Both head removal and the growing environment influenced the process of leaf senescence (Ho et al 1987). It was shown that while the absence of seeds affected partitioning and the rate of assimilation, as well as extending the period of assimilation of dry matter, reduced nitrogen and phosphorus, the total accumulation was the same in headed and deheaded plants (Figure 8.7) (Ho and Below 1989). Deheading led to accumulation of photosynthate and minerals in the vegetative tissues, while intact plants allocated large portions of nutrients to the seedhead.…”
Section: Barley Photosynthesis In Barley (Hordeum Vulgare)mentioning
confidence: 87%
“…In soybean (Glycine max), overall senescence of the leaves follows seed production. Removal of the flowers and fruits delayed senescence, but when reproductive structures were removed early in their development, a greater delay occurred than when older fruits were removed (Leopold et al 1959 Vegetative tissues become alternate sinks for nutrients after deheading, which delays senescence (data from Ho and Below 1989, 1983a. The leaves of continuously depodded (de-sinked) soybean plants, although dark green, showed lower photosynthetic rates than the yellowing leaves of the senescing control plants.…”
Section: Barley Photosynthesis In Barley (Hordeum Vulgare)mentioning
confidence: 99%
“…Rousseaux, Hall & Sánchez 1993). Experiments in which grain set was prevented demonstrated a consistent delay and/or slowing down of leaf senescence in oilseed species, including sunflower and soybean (Ho & Below 1989; Lindoo & Noodén 1977). In cereals, on the other hand, ear removal may delay or accelerate leaf senescence, depending on genotype (Thomas & Smart 1993).…”
Section: Roles Of the Overdraft Layermentioning
confidence: 99%